(untitled) (International Journal of Engineering and Computer Science, 2016)
A new number system, Perfect Difference Number System (PDNS), based on the mathematical notion of Perfect Difference Sets (PDS) is proposed. It is expected that PDNS will take its place in the family of other number systems and will benefit computer theory and applications